THE The influence of cooperative learning models type of make a-match on learning outcomes physics of matter impuls and momentum in class x YAPIM Sei Rotan private high school Y.S. 2023/2024 - Pinondang Hutapea; Marice Hotnauli Simbolon (Sean Institute, 2024)
This study aims to determine whether there is an effect of learning outcomes Physics by applying the make a-match type cooperative learning model in class x at high school state swasta YAPIM Sei Rotan Y.S. 2023/2024. This type of research is quasi experimental. The sample in this study consisted of 2 classes taken using the cluster random sampling technique, namely class X-2 as the experimental class which was taught using the Make A-Match Type Cooperative learning model and class X-3 as the control class which was taught using the Direct learning model. The instrument in this study used a multiple choice test, consisting of 20 questions consisting of 5 options (a, b, c, d,and e). Before the questions were tested on students, the instrument questions were first tested on students outside the sample, to determine validity, reliability, discriminating power, and level of difficulty. From the results of data analysis, it was obtained that the average pretest value for the experimental class was 44.53 with a standard deviation of 10.80 and the average value for the control class was obtained for pretest data of 41.25 with a standard deviation of 11.99. From the results of the statistical test t test for two parties, the price for tcount= 1.20 and ttable= 1.98 at a significant level α= 0.05 and dk= 62 is between dk= 60 and dk= 120. Because tcount < ttable this is states that the initial abilities of the two classes are the same. Then given different treatment, then the post-test was carried out, the average value of the experimental class by applying the Make A-Match Type Cooperative learning model was 78.59 with a standard deviation of 11.99 and the average post-test value for the control class by applying the Direct learning model was 67. 96 with a standard deviation of 9.14. Based on the results of the one-party t test statistic, the price for tcount= 3.988 and ttable= 1.669 at a significant level α= 0.05 and dk= 62 is between dk= 60 and dk= 120. Because tcount > ttable this shows a group of students who taught using the Cooperative learning model of the make a-match type obtained higher physics learning outcomes compared to the direct learning model on the subject matter of impulse and momentum in class x at high school state swasta YAPIM Sei Rotan Y.S. 2023/2024.